Influence of method of processing supplemental alfalfa on intake and utilization of dormant, bluestem-range forage by beef steers - B.A. Lintzenich; R.C. Cochran; E.S. Vanzant; J.L. Beaty; Robert T. Brandt Jr.; Tiruvoor G. Nagaraja; G. St. Jean (Kansas Agricultural Experiment Station Research Reports, 1993)
A digestion trial was conducted to determine the effect of method of processing supplemental alfalfa on the intake and utilization of dormant, bluestem-range forage. Supplement treatments were 1) control: no supplement; 2) ground and pelleted, suncured alfalfa; 3) ground and pelleted dehydrated alfalfa; and 4) longstem alfalfa hay. Bluestem forage intake (% BW), diet digestibility, and ruminal dry matter fill 4 hours after feeding were increased (P<.10) when supplemental alfalfa was fed, compared with no supplementation. Little difference was evident among different forms of supplemental alfalfa for most of the forage utilization characteristics measured. However, a weak trend (P=.18) was observed for increased intake of bluestem forage by the steers supplemented with dehydrated alfalfa pellets compared with suncured alfalfa pellets.
Keywords: Cattlemen' s Day; 1993; Kansas Agricultural Experiment Station contribution; no. 93-318-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 678; Beef; Supplements; Intake; Crude protein flow; Dormant range; Alfalfa